Laparoscopic versus Open Appendicectomy in a District Hospital (Medicine Today, 2022)
Introduction: Appendicitis is one of the most common clinical conditions requiring surgical intervention in day-to-day practice, which is indicated for both acute appendicitis and recurrent acute appendicitis. Appendicectomy can be performed using several surgical techniques like laparotomy (open), laparoscopic appendicectomy.Materials and Methods: We have done 110 cases in one year from July 2019 to June 2020.Results: Out of the 110 patients, 42 (38%) underwent laparoscopic surgery and 68 (62%) open appendicectomy.Conclusion: Female are predominant than male patients. Postoperative hospital stay, postoperative complications like wound infections are much less in laparoscopic procedure. The acceptance of laparoscopic appendicectomy gradually increases among the surgeons as well as the patients.Medicine Today 2022 Vol.34(1): 36-38